2022
DOI: 10.1111/jre.12983
|View full text |Cite
|
Sign up to set email alerts
|

Obesity influences the proteome of periodontal ligament tissues following periodontitis induction in rats

Abstract: Background and Objectives Many studies have been conducted to better understand the molecular mechanism involved with periodontitis progression. There has been growing interest in the potential impact of obesity on periodontitis onset and progression, but the mechanisms involved remain to be elucidated. The present study was designed to determine the impact of obesity on experimentally induced periodontitis in rats and identify novel pathways involved. Methods Sixteen Holtzman rats were distributed into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Interestingly, our group has recently demonstrated that obesity modifies the proteomic profile of PDL of rats subjected to experimental periodontitis, suggesting a critical effect of obesity on the PDL response to inflammation and tissue remodeling. Our study showed that obesity modulated the abundance of proteins related to periodontitis, such as spondin1, tartrate-resistant acid phosphatase, and vinculin [ 23 ]. Moreover, in another study, we observed the detrimental effects of obesity on the protein abundance of the PDL of rats exposed to orthodontic movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, our group has recently demonstrated that obesity modifies the proteomic profile of PDL of rats subjected to experimental periodontitis, suggesting a critical effect of obesity on the PDL response to inflammation and tissue remodeling. Our study showed that obesity modulated the abundance of proteins related to periodontitis, such as spondin1, tartrate-resistant acid phosphatase, and vinculin [ 23 ]. Moreover, in another study, we observed the detrimental effects of obesity on the protein abundance of the PDL of rats exposed to orthodontic movement.…”
Section: Discussionmentioning
confidence: 99%
“…The animals received a standard laboratory diet (Labina/Purina, Ribeirão Preto, Brazil) or a high-fat diet in addition to water ad libitum. They were randomly divided into two experimental groups: control animals (n = 3) and obese animals (n = 5), which comprised animals subjected to obesity induction by a high-fat diet, as previously described [ 23 , 24 ]. This high-fat diet had about 3.82 kcal/g and consisted of a mixture of standard rat chow and milk chocolate, peanuts, and sweet biscuits in a 3:2:2:1 ratio and contained 20 g of protein, 20 g of total fat, 48 g of carbohydrates, and 4 g of fiber per 100 g of diet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Animals that reached a body weight difference ≥15% compared to the body weight of healthy animals were considered obese. [20][21][22][23] To obtain these values, we averaged the weights recorded weekly for both healthy rodents and rodents on a hypercaloric diet, allowing a comparison over the weeks.…”
Section: Obesity Inductionmentioning
confidence: 99%
“…Microbial infection is the main cause of periodontitis, and excessive inflammation can destroy periodontal tissue [2]. The formation of osteoclasts leads to bone loss and stimulates the reabsorption of the alveolar bone, which ultimately leads to tooth loss [3]. Therefore, the inhibition of osteoclast differentiation is the way to treat periodontitis.…”
Section: Introductionmentioning
confidence: 99%